Effectiveness of Students' Motivation Factors in the Competency-Based Approach: A Case Study of Universities in Russia and Indonesia - Nuphanudin .; Aan Komariah; Tatiana Shvetsova; Zhanna Gardanova; Marina Podzorova; Dedy Achmad Kurniady; Marina Gladysheva; Olesya Dudnik; Richard Jonathan O. Taduran; Mikhail Kosov (Emerging Science Journal, 2022)
The study aimed to explore the influence of motivation factors on the development of professional competencies using Russian and Indonesian institutions of higher education as case studies. In pursuit of this objective, quantitative survey methodology was incorporated, and surveys were conducted during November and April of the 2018/2019 to 2021/2022 school years. The questionnaire was developed with a 10-point rating scale, aimed at addressing the development of students' professional competencies and the factors that motivate learning and competency development. Using the questionnaire, the level of professional competency development of students in Russian and Indonesian universities has been empirically analysed. The results of the study supported the spiral nature of students' professional competencies development, showing that the development of professional competencies follows a progressive and non-linear nature of component development. These results confirm that the process of professional competency development is structurally divided into separate, relatively independent stages reflecting sequential and gradual progression. The positive character of the influence of the balanced development level of intrinsic and extrinsic motivation factors on the formation of students' professional competencies has been established. The results of the research may prove useful for educational institutions and public administration bodies for the development of effective mechanisms for students' motivation within the framework of competency-based approach implementation in higher education. Doi: 10.28991/ESJ-2022-06-03-012 Full Text: PDF